Current status and role of programmed ventricular stimulation in patients without sustained ventricular arrhythmias and reduced ejection fraction: Analysis of the Japan cardiac device treatment registry database. Issue 1 (28th November 2020) - Yokoshiki, Hisashi; Shimizu, Akihiko; Mitsuhashi, Takeshi; Ishibashi, Kohei; Kabutoya, Tomoyuki; Yoshiga, Yasuhiro; Kohno, Ritsuko; Abe, Haruhiko; Nogami, Akihiko; ,
Abstract: Background: The aim of this study was to clarify the current status and role of programmed ventricular stimulation in patients without sustained ventricular arrhythmias and reduced left ventricular ejection fraction (LVEF). Methods: The follow‐up data of the Japan cardiac device treatment registry (JCDTR) was analyzed in 746 patients with LVEF ≦35% and no prior history of sustained ventricular arrhythmias who underwent de novo implantable cardioverter‐defibrillator (ICD) or cardiac resynchronization therapy with a defibrillator (CRT‐D) implantation between January 2011 and August 2015. Results: Electrophysiological study (EPS) with programmed ventricular stimulation had been performed before the device implant in 118 patients (15.8%, EPS group). During the mean follow‐up of 21 ± 12 months, the rate of freedom from any death and appropriate defibrillator therapy was not significantly different between EPS group (n = 118) and No EPS group (n = 628). NYHA class II‐IV, and QRS duration were negatively associated with performing EPS. Among patients in the EPS group, the rate of ventricular tachycardia (VT)/ventricular fibrillation (VF) induction was 48%. The inducibility was not a predictor of appropriate defibrillator therapy, whereas BNP ≧535 pg/mL and no use of amiodarone were significantly associated with a risk of the appropriate therapy. Conclusion: EPS for induction of VT/VF had been performed in about 16% of patients with reduced LVEF before primary prevention ICD/CRT‐D implantation. Elevated BNP levels and no use of amiodarone, but not inducibility of VT/VF, appeared to be associated with appropriate defibrillator therapy in these populations. Abstract : Electrophysiological study (EPS) had been performed with a rate of 15.8% in 746 patients with reduced ejection fraction (≦35%) who underwent primary prevention implantable cardioverter‐defibrillator (ICD) or cardiac resynchronization therapy with a defibrillator (CRT‐D) implant, based on the analysis of the Japan cardiac device treatment registry (JCDTR) database. Sustained ventricular arrhythmias were induced in about half of these patients, but the inducibility was not a predictor of appropriate defibrillator therapy. Elevated BNP levels and no use of amiodarone might be related to future appropriate defibrillator therapy in primary prevention ICD/CRT‐D patients with reduced ejection fraction (≦35%).